Butternut Squash (Curcubita moschata) House Development through the Implementation of the Eco-Techno Farming System as a Solution to Increase Family Income During Covid 19 Pandemic in Pudak Village Kumpeh Ulu District Muaro Jambi Regency - Tani, Sri Arnita Abu; Latief, Abdul; Syarif, Suhessy (Talenta Publisher Universitas Sumatera Utara, 2022)
The Covid-19 pandemic has greatly affected people's lives, especially women farmer from the Sibermas Mandiri Women's Farmer Group, Pudak Village, Kumpeh Ulu District, Muarojambi Regency. This pandemic has resulted in a decline in household income. Therefore, it is necessary to find a solution to increase their household income through the cultivation of Butternut Squash (Curcubita moschata) which currently has a large enough opportunity and market potential to become a business. In an effort to achieve this target, the Butternut Squash cultivation innovation can be implemented through the